Floral morphological and chemical analyses of Dienia flowers (Orchidaceae, Malaxidinae) relative to pollination processes - Hanna B. Margońska; Małgorzata Kozieradzka-Kiszkurno; Emilia Brzezicka; Łukasz P. Haliński; Kevin L. Davies (Scientific Reports)
Abstract Dienia is a small, pantropical genus of epidendroid Malaxideae orchids. The floral lip is upwardly directed and does not serve as a landing platform for pollinators. This role has been assumed by sepals and/or gynostemium or whole inflorescence. Information about the pollination and floral morphology of this genus is scarce. Field observations have revealed that the flowers are visited by small flies, midges, other small dipterans, ants, and mites etc. Preliminary observations have revealed that small liquid droplets of at least two types occur on the morphologically adaxial lip surface of Dienia: namely, simple secretions produced by epidermal cells, and cell sap released on the rupturing of raphide cells. These secretions were subjected to sequential organic solvent extraction and gas chromatography-mass spectrometry. Floral structures were investigated by means of scanning and transmission electron microscopy, and subjected to histochemical tests. The form of liquid droplets on the lip, as well as the presence of a food reward and the sequence of raphide development are reported here for the first time. Tree different form of calcium oxalate crystals were raported in Dienia ophrydis flowers.